Analisis Kualitas Tanah Sawah Pada Pergiliran Tanaman Padi dan Kacang Tanah Di Desa Sambueja Kecamatan Simbang Kabupaten Maros: Analysis of Rice Soil Quality On The Rotation Of Rice And Peanut Crops In Sambueja Village, Simbang District, Maros Regency - Aulia Luhtfyah Asbar; Asmita Ahmad (Jurnal Ecosolum, 2026)
Background. Soil quality refers to the soil’s capacity to sustain the growth and productivity of plants and animals while maintaining environmental functions. Therefore, soil management strategies must be adapted to site-specific conditions to minimize degradation. Aim. This study aimed to assess soil quality in land managed under a rice–peanut crop rotation system in Sambueja Village, Maros Regency. Method. A quantitative descriptive approach was employed, involving the collection of secondary data, site verification, and field surveys. Primary data were obtained through soil sampling and laboratory analyses of minimum data set parameters, including pH, total nitrogen (N), available phosphorus (P), organic carbon (C), cation exchange capacity (CEC), and soil macrofauna diversity. Macrofauna diversity was evaluated using the Shannon–Wiener index, and the Soil Quality Index (SQI) was determined through principal component analysis (PCA). Results. Correlation analysis revealed a significant positive relationship (p < 0.01) between soil pH and phosphorus content, as well as between clay content and macrofauna diversity. Conversely, macrofauna diversity and nitrogen content were negatively correlated at the 5% significance level. The scree plot indicated the eigenvalues for PCA1–PCA4, with SQI-PC1 (0.35) categorized as moderate, SQI-PC2 and SQI-PC3 as low, and SQI-PC4 as very low. The overall Comprehensive Soil Quality Index value (0.16) was classified as very low. Conclusion. Practices such as transporting and burning crop residues decrease the soil quality index by reducing soil organic matter, whereas incorporating crop residues into the soil during tillage helps maintain soil quality.